SPORTS PUBLICITY a practical approach. - Favorito, Joseph ([S.l.] : ROUTLEDGE, 2025)
In the fourth edition of his groundbreaking guide to communications in sports, Joe Favorito draws on knowledge gained from interviews with thought leaders from across the sports industry to introduce the skills, knowledge, and techniques needed to become a successful communicator. The book outlines the history of sports communications; explores the most important professional themes, topics, and issues; and highlights exciting opportunities for future development. With a strong emphasis on professional practice and the day-to-day realities of working in sports and entertainment, the book covers all the core functional areas such as digital and social media strategy, crisis management, creative writing, the value of audio storytelling, and the role of communications in business. This new edition includes more international and diverse case studies, interviews, and best practices, reflecting on how the sport communications business has become more integrated since 2020 and considering lessons learned through and after the COVID-19 pandemic. It also includes expanded coverage of cause marketing, athletes as brands, social media, multicultural media relations, gaming, and brand integration. No other book offers such a valuable insiders view of the sports communications industry or the importance of PR and media relations in building successful sports organizations. Sports Publicity: A Practical Approach is essential reading for all students working in sport business, marketing, or communications and any PR practitioner looking to improve their professional skills. The author maintains a podcast of updated best practices, The CUSP Show, which is widely available, as well as a blog of best practices at joefavorito.com. Both of these resources are perfect companions to this book.
Keywords: Sports -- Public relations; BUSINESS & ECONOMICS / Public Relations; SPORTS & RECREATION / General